USE OF METHOTREXATE IN PATIENTS WITH CALCIUM PYROPHOSPHATE CRYSTAL DEPOSITION DISEASE - M. S. Eliseev; S. A. Vladimirov; E. L. Nasonov (Научно-практическая ревматология, 2018)
Objective: to compare the efficacy of methotrexate (MTX) and colchicine in patients with chronic arthritis in calcium pyrophosphate crystal deposition disease (CPPDD).Subjects and methods. Data from a controlled prospective cross-sectional study of 10 patients (8 women and 2 men) with chronic arthritis in CPPDD are presented. In the initial period of treatment, all the patients were given colchicine 1 mg/day for 3 months, followed by a wash-out period for 1 month and then subcutaneous MTX 20 mg/week for 3 months. The diagnosis of CPPDD was made if there were calcium pyrophosphate crystals in synovial fluid and signs of chondrocalcinosis, as evidenced by joint X-ray and/or ultrasonography. DAS44, the swollen joint count (SJC) and tender joint count (TJC), pain intensity on a visual analog scale (VAS), the Health Assessment Questionnaire (HAQ) index, and serum C-reactive protein (CRP) levels were determined in all the patients at baseline, 3 months after the beginning of treatment with colchicine, after a wash-out period, and 3 months after the beginning of MTX treatment.Results and discussion. At baseline, mean DAS44 value was 2.47±0.27; SJC and TJC were 2.0±0.6 and 2.4±1.1, respectively; pain intensity was 55.2±12.3 mm; serum CRP level – 3.89±3.82 mg/l; HAQ – 1.1±0.3. Three months after colchicine therapy initiation, mean DAS44 value decreased to 1.76±0.28 (p = 0.004), SJC – to 1.4±0.5 (p = 0.048), TJC – to 1.6±1.35 (p = 0.023), pain intensity – to 42.0±13.2 mm (p = 0.023), CRP level – to 3.13±2.85 mg/l (p = 0.75), HAQ – to 0.95±0.3 (p = 0.041). Good response was achieved in 7 patients after 3 months of colchicine therapy. After the wash-out period, the mean DAS44 value was 2.08±0.26; SJC and TJC – 1.6±0.5 and 1.7±1.4, respectively; pain intensity – 46.5±9.8 mm; CRP level – 3.38±1.74 mg/l; HAQ – 1.3±0.34. Following 3 months of MTX therapy, mean DAS44 value decreased to 1.39±0.45 (p = 0.027), SJC – to 0.7±0.5 (p = 0.023), TJC – to 0.6±0.5 (p = 0.007), pain intensity – to 26.0±18.97 mm (p = 0.045), CRP level – to 2.87±2.06 mg/l (p = 0.75), HAQ – to 0.8±0.6 (p = 0.045). Two of the 3 patients with an insufficient effect of colchicine achieved DAS44 remission after MTX treatment; two patients attained remission after therapy with colchicine and developed an exacerbation of the disease when this drug was replaced by MTX.Conclusion. MTX 20 mg/week is as effective as colchicine in most cases and can be the drug of choice in patients with chronic arthritis in CPPDD if colchicine therapy is ineffective.